Leveraging the microbiome to combat antibiotic resistant gynecological infections - Tanya Kumar; Aryak Rekhi; Yumie Lee; Julielam Tran; Arlene Grace D. Nagtalon; Sidhant Rohatgi; Erika L. Cyphert (npj Antimicrobials and Resistance)
Abstract The vaginal resistome can be considered a collection of the resistant determinants in the vaginal microbiome. Here we review the vaginal resistome including the microbes and resistant genes harbored in common gynecological infections, vaginal microbes that participate in horizontal gene transfer, host factors that contribute to the resistome, and common therapies. Finally, we provide perspective on technologies that can be leveraged to study the vaginal resistome and remaining challenges.